Exploring Students’ Strategies in Dealing with Unfamiliar Vocabulary during a Listening Task in Higher Education - Amiruddin, Amiruddin; Satriani, Satriani; Bahri, Syamsul; Muslaini, Fadel (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Vocabulary is an essential component in listening comprehension. However, learners are often confronted with unfamiliar words that can hinder their overall understanding. This research aims to explore the strategies used by English as a foreign language (EFL) learners when they encounter unfamiliar vocabulary during listening tasks in the first semester of the English education department at Islamic University of As’adiyah, Sengkang. This qualitative research with a case study approach involved 13 first-semester students from the English Education study program. Data was gathered using a combination of think-aloud protocols (where students verbalized their thoughts while completing the task), listening to task recordings, and semi-structured interviews. Students listened to three authentic audio texts with varying levels of difficulty and challenging vocabulary. Thematic analysis revealed five main strategies used by students: (1) Contextual Inference (using clues from surrounding sentences or paragraphs), (2) Focus on Familiar Elements (ignoring unfamiliar words and concentrating on understood words/sentences), (3) Utilizing World Knowledge (connecting the content to their background knowledge), (4) Recording Keywords (writing down words that are thought to be important for later analysis), and (5) Searching for Phonological Cues (identifying words that sound similar to their native language or English that they know). Although contextual inference is the most common strategy, its effectiveness varies greatly depending on the language proficiency of the learners and the clarity of the context provided.